Mining engineering analysis - Bise, Christopher J. (Society for Mining, Metallurgy, and Exploration, 2003)
The bestseller sets the standard for university-level instruction of mining engineering principles. With a thoughtful balance of theory and application, the book gives students a practical working knowledge of all the concepts presented. Its utility extends beyond the classroom as a valuable field reference for practicing engineers and those preparing for the Mining/Mineral Professional Engineering Exam. This practical guidebook covers virtually all aspects of mine design and operations. It is an excellent reference for engineering students who are studying mine design or who require guidance.
Keywords: Mining engineering.; elektronické knihy; electronic books